AUDIT ENERGI DAN MONITORING BERBASIS IOT UNTUK PENINGKATAN EFISIENSI PENGGUNAAN LISTRIK DI ART CENTER DENPASAR - Putranto, Novian Bayu; Dharma, Agus; Rhamani Suryadhi, Putu Ayu (Jurnal SPEKTRUM; Vol 9 No 2 (2022): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2022.v09.i02.p10, 2022)
An energy audit is needed to find out energy saving opportunities (PHE) so that it will reduce the amount of electricity bills at the Denpasar Art Center which is used as a cultural performance center in Bali. A more specific location in this research is the Ksirarnawa Art Center Denpasar Building in the lighting section. The energy audit in this study is combined with an IoT-based electrical energy monitoring tool so that electricity usage can be monitored in real time. This IoT-based electrical energy monitoring uses Arduino Nano as a data processor as well as sending data to a site service called Thingspeak to record and display data from sensors. The sensors used are the ZMPT101B voltage sensor and the YHDC SCT 013-000 current sensor which are integrated with the NodeMCU as a module to connect to a wireless network. The results of the energy audit at the Denpasar Art Center got a potential Energy Saving Opportunity (PHE) of 33.6% with suggestions to related parties being to replace lamps using LEDs and to regularly set on/off times.